The Untapped Potential of Hybrid Fibre Coaxial Networks - Goddard, John (Journal of Telecommunications and the Digital Economy, 2014)
Australia has a number of hybrid fibre coaxial networks that pass about 3 million premises. These networks constitute an underutilized resource that could provide high quality, high speed broadband services to 7 million Australians at minimal cost. This has now been recognized in NBN Co.’s recent strategic review and the introduction of the multi-technology mix solution for the NBN. This paper describes how the hybrid fibre coaxial networks can provide all the required features of the NBN and the potential upgrade path to a future all-fibre access network.